Sebuah Tinjauan Pustaka dan Analisis Bibliometrik Resistensi Multidrug Therapy (MDT) pada Mycobacterium leprae - Sulthon Nurreza Setyawan; Syafri Musthofa; Isnawati Isnawati (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2026)
Background: Leprosy remains a global public health problem, and the emergence of resistance to Multidrug Therapy (MDT) poses a serious obstacle to eradication efforts.Objective: This study aims to systematically review the mechanisms of resistance, the types of drugs involved, and the diagnostic approaches, while mapping research trends through bibliometric analysis.Methods: The study was conducted using a Systematic Literature Review (SLR) method based on PRISMA guidelines with data sourced from Scopus for the 2015–2025 publication period. Of the 11,166 identified articles, only 16 met the inclusion criteria. Furthermore, a bibliometric analysis using the Bibliometrix R package on 2,214 publications was conducted to describe country scientific production, country production over time, co-occurrence, and word cloud.Results: The results showed that gene mutations rpoB, folP1, and gyrAis a major determinant of resistance to rifampin, dapsone, and ofloxacin, while new mechanisms such as partial duplication folP1 and compensatory mutations in rpoC indicates increasingly complex resistance patterns. India and Brazil contribute the most publications, in line with their high disease burden, while Indonesia's figures are relatively low despite being a major endemic country.Conclusion: This study emphasizes that MDT resistance requires more precise strategies, including strengthening molecular surveillance, genetic-based diagnostics, and developing locally tailored therapeutic policies. Increased research capacity and international collaboration are also needed to accelerate the achievement of global leprosy elimination targets.